Exploring Bacterial Microcompartments in the Acetogenic Bacterium Acetobacterium woodii - Chowdhury, Nilanjan Pal; Alberti, Lydia; Linder, Mark; Müller, Volker (Frontiers in Microbiology, 2020)
The strictly anaerobic acetogenic bacterium Acetobacterium woodii is metabolically diverse and grows on variety of substrates which includes H2+CO2, sugars, alcohols and diols. It is unique in producing bacterial microcompartments (BMC) during growth on different substrates such as propanediol, 2,3-butanediol, ethanol or fructose. In this study, we analyzed the genetic organization and expression of the BMC genes within the A. woodii genome, the previously described 18 gene pdu cluster as well as four other cluster potentially encoding one or two shell proteins. Expression analysis of respective gene clusters revealed that the pdu gene cluster is highly expressed during growth on 1,2-PD, 2,3-BD, ethanol and ethylene glycol. The promoter region upstream of the pduA gene was identified and used to establish a reporter gene assay based on chloramphenicol acetyl transferase as a reporter protein. The reporter gene assay confirmed the qPCR data and demonstrated that 1,2-PD is superior over ethanol and ethylene glycol as inducer. BMCs were enriched from cells grown on 2,3- BD and 1,2-PD and shown to have typical structure in electron micrographs. Biochemical analyses revealed several of the protein encoded by the pdu cluster to be part of the isolated BMCs. These data demonstrate a very unique situation in A. woodii in which apparently one BMC gene cluster in expressed during growth on different substrates.